Composting of municipal biosolids: effect of bulking agent particle size on operating performance. Issue 3 (1st May 2006) - Raichura, Ash; McCartney, Daryl
Abstract : Woodchips, prepared from wood waste obtained from a pallet manufacturer, were used to determine the effect of bulking agent particle size on compost pile performance. The three treatments investigated used coarse, medium, or fine woodchips. Characteristic particle sizes were 40, 13, and 5.2 mm for the coarse, medium, and fine material, respectively. All recipes were made using one part biosolids to 2.5 parts woodchips ( v : v ) at a target moisture content of 60%. Finer woodchips resulted in thermophilic temperature values being reached sooner, being sustained for a longer time (>95 d), and recovering more quickly after rainfall events. Finer woodchips also resulted in lower moisture loss over the experimental period. Based on the experimental observations, it was assumed decreased tortuosity in the coarse woodchip material led to higher ventilation rates as compared to the finer material. Further experimental work is required to confirm this. The authors' recommend operators characterize feedstock bulking agent particle size distribution, particularly at facilities purchasing bulking agents for their operations. Key words : compost, municipal biosolids, woodchips, particle size, bulking agent, temperature.